"He escrito, pues, lo que he escrito". Sarmiento as a Latin American Travelling Subject: a Reading of the Prologue to "Viajes por Europa, África i América, 1845-1847" - Errázuriz, Rebeca (Meridional. Revista Chilena de Estudios Latinoamericanos, 2014)
The following paper makes an analysis of the prologue in Sarmiento’s travel book under the assumption that the traveler’s discourse elaborates an hermeneutic process of both foreign space and foreign culture. Therefore, the prologue’s analysis allows us to understand the ways in which Sarmiento justifies the writing and the publishing of his travel book as a production of useful knowledge regarding the spaces of civilisation.